2022
DOI: 10.1080/22221751.2022.2054368
|View full text |Cite
|
Sign up to set email alerts
|

RT-LAMP assay for rapid detection of the R203M mutation in SARS-CoV-2 Delta variant

Abstract: The highly infectious Delta variant strain of SARS-CoV-2 remains globally dominant and undermines COVID-19 vaccines. Rapid detection of the Delta variant is crucial for the identification and quarantine of infected individuals. In this study, our aim was to design and validate a genotyping RT-LAMP method to detect Delta variants specifically. R203M in the N gene of SARS-CoV-2 was chosen as the Delta variant-specific mutation for genotyping. To target the R203M-harboring region and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The authors used molecular beacons and additional oligonucleotides to block nucleic acids. Another study reported an RT-LAMP-based genotyping method focusing on R203M in the SARS-CoV-2 N gene to detect Delta variants specifically 33 . Although the test did not use additional oligonucleotides, the excellent ability to distinguish between Delta and non-Delta variants occurred by calculating a ratio between the Cts of two different reactions per sample.…”
Section: Discussionmentioning
confidence: 99%
“…The authors used molecular beacons and additional oligonucleotides to block nucleic acids. Another study reported an RT-LAMP-based genotyping method focusing on R203M in the SARS-CoV-2 N gene to detect Delta variants specifically 33 . Although the test did not use additional oligonucleotides, the excellent ability to distinguish between Delta and non-Delta variants occurred by calculating a ratio between the Cts of two different reactions per sample.…”
Section: Discussionmentioning
confidence: 99%
“…According to the fluorescence signals, with as low as 10 0 copies of the SARS-CoV-2 mutant (MT) RNA, the L452R mutation could be identified (Figure ). The single-copy sensitivity is the highest sensitivity that can be achieved theoretically, and is also the highest sensitivity as compared to the available SARS-CoV-2 genotyping assays. According to the reports, the nucleic acid amplification and probe-based assays had sensitivities in the range of tens to hundreds of copies per reaction. The CRISPR-based assays had sensitivities of around 10 copies per reaction. , By fully utilizing Pf Ago’s specific recognition and cleavage property, the RPA- Pf Ago method exhibited a solid advantage in terms of sensitivity with which a single copy could be sufficient for the mutation identification (Figure ). The single-copy sensitivity is the highest sensitivity that can be achieved theoretically and is also the highest sensitivity as compared to the available SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…Sherrill-Mix et al (2021) 32 used a pair of molecular beacons with RT-LAMP to specifically detect B.1.1.7 and other variants that contain a characteristic deletion in the gene encoding the viral spike protein. Yang et al (2022) 33 designed and validated a genotyping RT-LAMP method to detect Delta variants specifically by detecting the R203M in the N gene of the SARS-CoV-2 Delta variant. Both studies reported good specificity and a 95% confidence limit of detection (LOD 95) at approximately 4.0 × 10 2 copies per reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Although it presents significant advantages in terms of simplicity, time, cost, and instrumental need, the proposal to use LAMP to infer variants of SARS-CoV-2 is still discrete. 33 designed and validated a genotyping RT-LAMP method to detect Delta variants specifically by detecting the R203M in the N gene of the SARS-CoV-2 Delta variant. Both studies reported good specificity and a 95% confidence limit of detection (LOD 95) at approximately 4.0 × 10 2 copies per reaction.…”
Section: Analytical Performancementioning
confidence: 99%
See 1 more Smart Citation